The Influence of Creativity and Product Innovation on Marketing Performance: The Mediating Roles of Technology Adoption and Competitive Advantage in MSMEs - Latief, Fitriani; Mubyl, Mutiarini; Firman, Ahmad; Karnawati, Tin Agustina; Fathorrahman; Sidi, Agus Purnomo (Universitas Brawijaya, Indonesia, 2025)
The rapid growth of MSMEs in Indonesia underscores the urgency for innovation-driven strategies to remain competitive. This study investigates the influence of creativity and product innovation on marketing performance, with technology adoption and competitive advantage serving as mediating variables. A quantitative approach was used, collecting data from 87 MSME owners in Malang City through purposive sampling. Structural Equation Modeling with SmartPLS 4.0 was employed to analyze measurement and structural models. The results show that creativity has a direct and significant effect on marketing performance and competitive advantage, while product innovation significantly influences technology adoption and competitive advantage, but not marketing performance directly. Mediation analysis reveals that competitive advantage mediates the relationship between creativity and marketing performance, while technology adoption mediates the effect of product innovation on marketing performance. These findings highlight the strategic importance of enhancing digital readiness and leveraging creativity to build competitive advantages. The novelty of this study lies in the integration of two mediators (technology adoption and competitive advantage) to explain the indirect effects of creativity and innovation on marketing outcomes in MSMEs. This provides practical insights for policymakers and business practitioners aiming to improve MSME competitiveness in emerging markets.